2001
DOI: 10.1093/carcin/22.8.1257
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant cell cycle checkpoint function in transformed hepatocytes and WB-F344 hepatic epithelial stem-like cells

Abstract: Cell cycle checkpoints are barriers to carcinogenesis as they function to maintain genomic integrity. Attenuation or ablation of checkpoint function may enhance tumor formation by permitting outgrowth of unstable cells with damaged DNA. To examine the function of cell cycle checkpoints in rat hepatocarcinogenesis, we analyzed the responses of the G (1), G (2) and mitotic spindle assembly checkpoints in normal rat hepatocytes, hepatic epithelial stem-like cells (WB-F344) and transformed derivatives of both. Nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 52 publications
1
13
0
Order By: Relevance
“…4B). A similar emptying of the S-phase compartment following irradiation of WB-F344 cells with 8 Gy of ␥-rays was observed by Kaufmann et al (6).…”
Section: Distribution Of Cells In Phases Of the Cell-cyclesupporting
confidence: 82%
See 2 more Smart Citations
“…4B). A similar emptying of the S-phase compartment following irradiation of WB-F344 cells with 8 Gy of ␥-rays was observed by Kaufmann et al (6).…”
Section: Distribution Of Cells In Phases Of the Cell-cyclesupporting
confidence: 82%
“…Trosko 4), and Trosko and Ruch (5), have reported on extensive studies of the capacity of these cells to communicate with one another via gap junctional intercellular communication (GJIC) and the impact of GJIC on carcinogenesis. Kaufmann et al (6) have examined the influence of the number of in vitro passages (generations) of WB-F344 cells on their G 1 and G 2 checkpoint function following exposure to ionizing radiation (IR). This cell line has also been used to examine effects imparted by irradiated cells on their unirradiated neighbors, also known as bystander cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Cell lysates were prepared as described in [14]. T-cells after stimulation were incubated in the lysis buffer (150 mmol NaCl, 20 mmol TRIS, 10 % glycerol, 1 % Triton X-100, 5 mmol EDTA, 50 mmol NaF, 1mmol PMSF) for 30 min on ice.…”
Section: Western Blottingmentioning
confidence: 99%
“…Prevention of telomere erosion by ectopic expression of the catalytic subunit of human telomerase (hTERT) has been shown to prevent crisis in cells expressing SV40 large T antigen or HPV16E6 oncoprotein [7-10]. Normal diploid human fibroblasts expressing hTERT have been reported to maintain a normal karyotype and preserve cell cycle checkpoint function for at least 200 population doublings [11,12], although others have suggested that otherwise normal telomerase-expressing human fibroblasts do display alterations in expression of tumor suppressor genes, growth characteristics, and transient genetic instability [13-16] These studies have failed to directly address the question as to whether cells can maintain a stable genome in the absence of a functional DNA damage induced G 1 checkpoint.…”
Section: Introductionmentioning
confidence: 99%